2021
DOI: 10.1038/s41419-021-04228-z
|View full text |Cite
|
Sign up to set email alerts
|

ELK4-mediated lncRNA SNHG22 promotes gastric cancer progression through interacting with EZH2 and regulating miR-200c-3p/Notch1 axis

Abstract: Long non-coding RNAs (lncRNAs) play important regulatory roles in the initiation and progression of various cancers. However, the biological roles and the potential mechanisms of lncRNAs in gastric cancers remain unclear. Here, we report that the expression of lncRNA SNHG22 (small nucleolar RNA host gene 22) was significantly increased in GC (Gastric Cancer) tissues and cells, which confers poor prognosis of patients. Knockdown of SNHG22 inhibited the proliferation and invasion ability of GC cells. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Luan and colleagues recently reported that ALMS1-IT1 promoted the malignant progression of lung adenocarcinoma through AVL9-mediated activation of the cyclin-dependent kinase pathway ( 73 ). SNHG22 has been detected to be overexpressed and to act as an oncogene in multiple cancers, including CRC ( 74 , 75 ). Yao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Luan and colleagues recently reported that ALMS1-IT1 promoted the malignant progression of lung adenocarcinoma through AVL9-mediated activation of the cyclin-dependent kinase pathway ( 73 ). SNHG22 has been detected to be overexpressed and to act as an oncogene in multiple cancers, including CRC ( 74 , 75 ). Yao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials have also assessed the anticancer efficacy of Notch inhibitors ( 56 ). Notably, the interplay of lncRNA molecules with Notch pathway-related molecules regulates a variety of malignant phenotypes of tumors ( 23 25 ). Therefore, this study is based on the lncRNA profiles from Notch signaling and aims to establish a model with the ability to predict prognosis and immune response and assist in the screening of sensitive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA molecules were commonly present in tumors as a double-edged sword of driving tumor development or inhibiting progression ( 19 22 ). Previous studies have confirmed that lncRNA could govern key ligands in the Notch pathway to achieve tumor control, such as breast cancer, renal cell cancer, and gastric cancer ( 23 25 ). Nevertheless, the comprehensive landscape of the Notch pathway-related lncRNA in CRC remains elusive, and we hope to endue Notch pathways with a novel character and clinical application through functional lncRNA analysis.…”
Section: Introductionmentioning
confidence: 92%
“…LncRNA Small Nucleolar RNA host gene 22 (SNHG22) has been found to play a role in the migration and invasion of several carcinomas, such as gastric cancer, hepatocellular carcinoma, and breast cancer. 16 , 17 , 18 However, the contribution of SNHG22 to the biological function of trophoblasts remains unclear.…”
Section: Introductionmentioning
confidence: 99%